A Comparison of the Effects of Estradiol and the Soy Phytoestrogen Genistein on Liver Lipid Content of Chickens - Stevenson, L.M.; Hess, J.B.; Oates, S.S.; Berry , W.D. (International Journal of Poultry Science, 2014)
Abnormal liver lipid accumulation has a negative effect on health. It is associated with many factors including estrogen, alcohol consumption, metabolic problems and obesity. Research has shown that soy phytoestrogens may have a protective effect against liver lipid accumulation in rats. Exogenous estrogen has been used experimentally to induce liver lipid accumulation in chickens. A series of studies was performed to determine if genistein had a protective effect against liver lipid accumulation induced by exogenous estrogen. Three experiments were performed using different types and ages of chickens; old hens, young hens and male broiler chicks. Birds were randomly selected and divided into six treatment groups. All treatments doses were dissolved in dimethyl sulfoxide (DMSO) with sesame seed oil as a carrier. Genistein doses were given by a daily oral gavage for fourteen days. Estrogen doses were given by injection in the subcutaneous tissue in the back of the neck three times during the experiment. There were no significant differences in most of the items measured. There was a significant difference in the liver weight (p = 0.035) and relative liver weight (p = 0.01) for the study involving male broiler chicks. The amount of genistein in plasma and liver samples was measured by HPLC. There was a significant difference in the amount of genistein in the plasma of the old hens after treatment with genistein (p = 0.01). There was also a significant difference in the amount of genistein in the liver of the old hens (p = 0.003) and male broiler chicks (p = 0.005) after treatment with genistein.